A Novel Design and Implementation of New Double Feynman and Six-correction logic (DFSCL) gates in Quantum-dot Cellular Automata (QCA) - Waheed, Sajjad; Aktar, Sharmin; Bahar, Ali Newaz (European Scientific Journal, ESJ, 2017)
In recent years, quantum cellular automata (QCA) have been used widely to digital circuits and systems. QCA technology is a promising alternative to CMOS technology. It is attractive due to its fast speed, small area and low power consumption. The QCA offers a novel electronics paradigm for information processing and communication. It has the potential for attractive features such as faster speed, higher scale integration, higher switching frequency, smaller size and low power consumption than transistor based technology. In this paper, Double Feynman and Six-correction logic gate (DFSCL) is proposed based on QCA logic gates: MV gate and Inverter gate. The proposed circuit is a promising future in constructing of nano-scale low power consumption information processing system and can stimulate higher digital applications in QCA.